Disaster and rehabilitation in civil engineering - Reza Pahlevi, Munirwan; Putra Jaya, Ramadhansyah; Aizat, Mohd Taib (Popular Scientist, 2024)
We are excited to announce the launch of the 2024 edition of the Disasters in Civil Engineering and Architecture journal. In this first volume, the issue focuses on the impact of natural and man-made disasters on civil infrastructure and the methods employed to rehabilitate and restore damaged systems. Civil engineers play a critical role in disaster management, from risk assessment and mitigation strategies to post-disaster recovery.